Pengaruh Persentase Minyak Kayu Putih Dan Nilai Oktan Bahan Bakar Terhadap Getaran Mesin Dan Emisi Gas Buang - Muhammad Alfiadi Triswial Arsy; Santoso Santoso (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Vehicles in Indonesia continue to increase every year which has an impact on fuel consumption and air pollution. Vehicle gas emissions are the biggest contributor to air pollution. This research method uses experiments with gas analyzers and vibration meters. Variations in octane values ​​of 90 and 92 with mixture percentages of 10%, 18%, 22% at 2000 to 5000 rpm. Test results were analyzed using two-way ANOVA. The research results showed that at RON 90 there was a change in CO and HC with the best percentage, in the 18% mixture the CO was 0.29% and HC 96ppm compared to the 10% and 22% mixture. At RON 92 there was a change in CO and HC at the best percentage, namely a mixture of 18%, data obtained for CO was 0.19% and HC was 62 ppm. So the reduction in CO and HC levels occurs in the ideal mixture by 18% at RON 90 and 92.